Can 4 weeks of real-world active breaks improve glycaemic management in sedentary adults with type 1 diabetes? The EXTOD-Active randomised control trial protocol - Samuel J E Lucas; Parth Narendran; Beverley M Shields; Robert C Andrews; Sam N Scott; Katie Hesketh; Matthew Cocks; Joseph G Jenkins; Catarina Rendeiro (BMJ Open Sport & Exercise Medicine)
Sedentary behaviour is associated with an increased risk of cardiovascular disease and all-cause mortality in individuals with type 1 diabetes (T1D). Recent laboratory-based research suggests that breaking up prolonged sedentary periods improves glycaemic markers in people with T1D. However, the effects of breaking up sedentary behaviour for prolonged periods in real-world settings remain unknown. This study aims to assess the effect of 4 weeks of active breaks on time spent within the target glycaemic range (time in range (TIR), 3.9–10.0 mmol/L) in adults with T1DAdults with T1D (n=118) who are sedentary for ≥8 hours per day will first complete a 7-day baseline assessment. Participants will then be randomised into either a control group (maintenance of habitual lifestyle) or an intervention group, where active breaks (3 min of self-paced walking every 30 min between 09:00 and 17:00, Monday through Friday) will be prescribed for 4 weeks. Activity levels (activPAL), TIR (via continuous glucose monitor), insulin dose and carbohydrate intake will be monitored throughout. The effect of active breaks on TIR will be compared between baseline and week 4, with data analysed using analysis of covariance (ANCOVA).The trial has been approved in the UK by the West Midlands-Solihull Ethics Committee (22/WM/0221). The findings from the study will be disseminated through peer-reviewed journals and presentations at national and international scientific conferences.Trial registration numberNCT05706298.